Boligpolitikkens historie - et upåagtet forskningsområde - Bro, Henning (Historisk Tidsskrift, 2013)
The History of Housing Policy: A Neglected Field of ResearchThe present article surveys historical studies in Denmark and internationally on housing and housing policy after 1850. Research on the housing initiatives of public authorities before and especially after World War I has until recently been sparse in Denmark compared to other countries in Central and Northwest Europe. Likewise, there are but few analyses of housing policy in a broader European perspective. Björn Linn, a Swedish scholar, elucidated the subject in his 1974 architectural and historical study Storgårdskvarteret (Housing Estates). There are also reports from three international workshops published in Housing Strategies in Europe 1880-1930 (1992). Before World War I housing policy in western European countries was guided largely by liberalist principles. It was only after 1914 that state and municipal authorities curtailed the total dominance of free market forces in the housing sector by launching their own housing projects, subsidizing private and nonprofit construction, and the regulation of rent. Some specialists see this break only as a temporary effect of entirely extraordinary conditions during and after World War I and find the real early roots of post-World War II housing regulation in the 1930s. However, the most recent Danish research on the welfare state traces the origins of present-day housing policy back to the period during and after the First World War. The housing policy initiatives of state and some municipal authorities in Denmark from 1850 to 1930 are closely examined by the author of the present article in a recent doctoral thesis: Boligen mellem natvægterstat og velfærdsstat (Housing: From Night Watchman to Welfare State), University of Copenhagen, 2006. The dissertation studies policy and practice both at the state level, and especially in the two core communes of the capital, Copenhagen and Frederiksberg, as well as in two smaller, selected communes: Nykø;bing on the island of Falster and Lyngby, a town north of Copenhagen. During the period from around 1850 to 1890 state as well as municipal authorities limited themselves to minimal regulations dealing with the material aspects of construction. The matter of improving housing conditions among the working class was left to middle class philanthropy or the initiatives of housing societies based on the idea of private help to self-help. From 1890 to 1914 the provision of housing and the level of rent continued to function on a market basis. The state, however, began to provide some assistance to building societies based on self-help in a development that ran quite parallel to contemporary social reforms. The Social Democratic labour movement was now setting the agenda for housing policy among other social reforms at both the local and national level. In the big city communes, where the Social Democrats were strongest, they attempted to directly implement a far-reaching welfare policy along with the Social Liberal Party (Det Radikale Venstre). Council housing construction played a central role in their strategy of “municipal socialism,” but its demands were too drastic in the context of a still sacred private housing market to gain the support of even the Social Liberals, and nothing came of it. During the period from 1914 to 1930 the housing market was weakened by the war and the post-war crisis. As a result of a further increase in the number of urban workers, both blue and white collar, the Social Democrats grew stronger and consolidated their position, periodically either as a coalition partner in the government or as its parliamentary support party, or even as government party. In most of the larger urban municipalities it attained a majority of the council seats. At both the national level and particularly in the larger cities it forced through a striking break with liberalist housing policy. Between 1916 and 1928 various kinds of state subsidies to housing construction were enacted, while many large communes followed suit by implementing municipal housing projects and providing subsidies to construction and housing societies as well as to certain types of private tenement dwellings. Public housing regulations were established along with other direct forms of intervention in the housing market. Urban councils introduced purposeful and effective planning of housing development. Housing policy carried out in the period from 1916 to 1930 formed the foundation for the housing policies of the later universalistic welfare state. State intervention and the complex of welfare reforms in the 1930s were developments based on the experience gained during and after World War I. State construction subsidizing was revitalized in 1933. It was expanded and supplemented with rent subsidies in 1938. Rent regulation was resumed in some city communes in 1937, resulting in a rent ceiling in 1939. The urban planning law of 1938 provided the legal framework for urban planning that had already been put into practice by the big cities in the previous period. The housing shortage during the German Occupation (1940-1945) spurred further schemes for construction subsidies. Housing policy culminated in the final years of the 1940s and throughout the 1950s with massive public subsidies to construction and housing societies as well as to private construction under various forms. Translated by Michael Wolfe